An Assessment of the Trainee Teachers’ Attitude towards ICT (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Recent technological advancements have altered the world outside and within the classroom, making these topics more engaging and relevant to pupils. The expectations placed on schools have evolved in response to changes in how knowledge and information are applied and disseminated. In recent years, researchers in the field of education have been more curious in the effects of incorporating information and communication technology (ICT) into the classroom setting. In light of this, the author of this piece set out to determine how students in teacher preparation programmes feel about information and communication technologies (ICT) and whether or not this feeling differs across demographic categories (gender, marital status, level of computer literacy). The study included 500 preservice teachers from B.Ed. programmes in Paschim and Purba Medinipur. The sample was picked using a method called Simple Random Sampling. Samuel Gnanamuthu and Krishnakumar R. developed and validated the Student Teachers' Attitude Towards ICT Scale. Twenty items make up the Student Teachers' Attitude Towards ICT Scale, each with five possible responses: Strongly Agree, Agree, Undecided, Disagree, and Strongly Disagree. The study's findings show that overall, student teachers have a positive outlook on ICT, but that there are substantial differences in outlook between married and unmarried student teachers. The attitudes of student instructors who are familiar with computers and those who are not are quite different from one another.